نموذج کمی مقترح لاستخدام بيانات التكاليف في تخطيط الأسعار على المستوى القومی - احمد هشام (Dirasat in Economics and Business, 1984)
The purpose of this paper is to explain the principal role which is played by the Central Unit for planning and Public Enterprises in price determination on a na anal level basis. The modci used in thi. paper is a mathematical model suggest about fifteen years ago This model is used uusacveral as sumptions. Some of these assumptions deal with the costing data available within the cconomic unit records, while other assumptions deal with some other data not available in the traditional accounting system. However, some of these assumptions could be eliminated through some more searching and inSolution The suggested model could be empirically applied through some kind of on using a Computer system Note: For more details, please see the full text of this article which is published in the Arabie section this 195